2013
DOI: 10.1155/2013/597563
|View full text |Cite
|
Sign up to set email alerts
|

Management and Followup of Complicated Crown Fractures in Young Patients Treated with Partial Pulpotomy

Abstract: Two cases of young patients with traumatized permanent teeth having complicated crown fractures are reported. Endodontic management included partial pulpotomy by the Cvek technique; restorative management included resin restoration and reattachment of the teeth fragments. Treatments were considered successful in all cases according to the following criteria: absence of clinical symptoms, absence of X-ray signs of pathology, and presence of pulpal vitality 6 to 25 months after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…23 Moreover, both in vitro and in vivo studies found that it does not have any inhibitory effects on the proliferation and differentiation of dental pulp stem cells. 21,[24][25][26] Limitations of dental materials used for pulp capping include treatment failure caused by bacteria entry though the fracture lines 27 and the effect of a humid environment, which can reduce their sealing ability. iRoot BP Plus is produced using bioceramic F I G U R E 3 An example of a successful case involving a 9-year-old boy with a complicated crown fracture in the left incisor.…”
Section: Discussionmentioning
confidence: 99%
“…23 Moreover, both in vitro and in vivo studies found that it does not have any inhibitory effects on the proliferation and differentiation of dental pulp stem cells. 21,[24][25][26] Limitations of dental materials used for pulp capping include treatment failure caused by bacteria entry though the fracture lines 27 and the effect of a humid environment, which can reduce their sealing ability. iRoot BP Plus is produced using bioceramic F I G U R E 3 An example of a successful case involving a 9-year-old boy with a complicated crown fracture in the left incisor.…”
Section: Discussionmentioning
confidence: 99%
“…After the advent of Ellis Classification, World Health Organisation (WHO) developed a classification in 1978, which is almost similar to Ellis Classification, but it avoids the use of eponyms and therapeutic considerations [4]. It was used only for descriptive purposes and used mostly by Health professionals of other fields [5].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Her iki olguda da geri dönüşümsüz pulpa iltihabını işaret edecek şekilde ağrının bulunması, pulpal ekspozürün 1 mm'nin üzerinde olması ve travmatik yaralanmaların üzerinden uzun süre geçmesi nedeni ile kök-kanal tedavisi uygulanmasına karar verilmiştir. Kök-kanal sistemindeki mikroorganizmaların elimine edilmesi için mekanik preparasyonun yanında irrigasyon solüsyonlarının kullanılması, ardından kalsiyum hidroksit içeren medikamentlerin kullanımı tavsiye edilmektedir.…”
Section: Discussionunclassified